Performance indicators for public mental healthcare: a systematic international inventory - Lauriks Steve; Buster Marcel CA; de Wit Matty AS; Arah Onyebuchi A; Klazinga Niek S (BMC, 2012)
Abstract Background The development and use of performance indicators (PI) in the field of public mental health care (PMHC) has increased rapidly in the last decade. To gain insight in the current state of PI for PMHC in nations and regions around the world, we conducted a structured review of publications in scientific peer-reviewed journals supplemented by a systematic inventory of PI published in policy documents by (non-) governmental organizations. Methods Publications on PI for PMHC were identified through database- and internet searches. Final selection was based on review of the full content of the publications. Publications were ordered by nation or region and chronologically. Individual PI were classified by development method, assessment level, care domain, performance dimension, diagnostic focus, and data source. Finally, the evidence on feasibility, data reliability, and content-, criterion-, and construct validity of the PI was evaluated. Results A total of 106 publications were included in the sample. The majority of the publications (n = 65) were peer-reviewed journal articles and 66 publications specifically dealt with performance of PMHC in the United States. The objectives of performance measurement vary widely from internal quality improvement to increasing transparency and accountability. The characteristics of 1480 unique PI were assessed. The majority of PI is based on stakeholder opinion, assesses care processes, is not specific to any diagnostic group, and utilizes administrative data sources. The targeted quality dimensions varied widely across and within nations depending on local professional or political definitions and interests. For all PI some evidence for the content validity and feasibility has been established. Data reliability, criterion- and construct validity have rarely been assessed. Only 18 publications on criterion validity were included. These show significant associations in the expected direction on the majority of PI, but mixed results on a noteworthy number of others. Conclusions PI have been developed for a broad range of care levels, domains, and quality dimensions of PMHC. To ensure their usefulness for the measurement of PMHC performance and advancement of transparency, accountability and quality improvement in PMHC, future research should focus on assessment of the psychometric properties of PI.